Metal-free synthesis of bisthiophene-core donor acceptor organic photosensitizers for dye-sensitized solar cells. Issue 39 (30th September 2015) - Bonaccorso, Carmela; De Rossi, Francesca; Panigati, Monica; Fortuna, Cosimo G.; Forte, Giuseppe; Brown, Thomas M.; Farinola, Gianluca M.; Musumarra, Giuseppe
Abstract: Three novel donor-π-acceptor molecules with a bis-thiophene core have been synthesized through a simple and versatile metal-free synthetic procedure. Study of their optical and electrochemical properties, and a preliminary evaluation of their use as dyes in dye sensitized solar cells (DSSC) are presented. The proposed synthetic protocol results in a drastic reduction of the size and complexity of the sensitizer molecule, possibly enabling cost decrease by overall yield improvement and easy scalability. Particular attention has been paid to limit the environmental impact by reducing the number of synthetic steps and especially avoiding the use of organometallic reactions. Graphical abstract: